Epidemiological Characterisation of Chronic Diseases Among Civil Servants in Hebei Province, China: A Cross-Sectional Real-World Study of Approximately 50,000 Adults - Pan X; Wang S; Jia B; Yue L; Chen S (Dove Medical Press, 2024)
Xiaoyu Pan,1,2 Shuqi Wang,1,2 Boying Jia,1,2 Lin Yue,1,3 Shuchun Chen1,2 1Department of Internal Medicine, Hebei Medical University, Shijiazhuang, Hebei, People's Republic of China; 2Department of Endocrinology, Hebei General Hospital, Shijiazhuang, Hebei, People's Republic of China; 3Department of Endocrinology, The Third Hospital of Shijiazhuang, Shijiazhuang, Hebei, People's Republic of ChinaCorrespondence: Shuchun Chen, Department of Endocrinology, Hebei General Hospital, Shijiazhuang, People's Republic of China, Tel/Fax +86 31185988406, Email chenshuc2014@163.comBackground: The objective of this investigation was to explore the health status and epidemiological features of civil servants working in Hebei Province, China.Methods: Data was collected through a cross-sectional survey that involved 50,039 adult civil servants in Hebei Province. The research was conducted at the Hebei Provincial Medical Examination Centre and included inquiries about demographics, health behaviours, chronic illnesses, and abnormal check-up indicators. Statistical data were used to determine the prevalence of chronic diseases and abnormal health examination indicators. Subgroup analyses by sex were then conducted to calculate the similarities and differences in health status between men and women.Results: The findings of the survey indicate that 14.2% of individuals who work in civil service suffer from obesity. Additionally, a considerable proportion of this group display poor health behaviours, including smoking and alcohol consumption. Hypertension (21.03%), dyslipidaemia (10.88%), and diabetes mellitus (8.56%) were identified as the top three chronic diseases, while cardiovascular diseases were prevalent at 6.27% among civil servants. Ultrasound showed a high prevalence of fatty liver, non-smooth gallbladder and liver cysts (44.61%, 33.24% and 23.26% respectively). The occurrence of pulmonary nodules was alarmingly high at 88.48%, while thyroid nodules were found in as much as 62.65% of patients. Abnormal E/A values≤ 1, prostate hyperplasia, breast nodules, and carotid plaques were also prevalent, with percentages ranging from 46.76% to 63.04%. In subgroup analyses by gender, the prevalence of chronic diseases and abnormal screening indicators was consistently higher in men than in women, with the exception of thyroid nodules and thyroid surgery.Conclusion: The survey revealed a large proportion of civil servants in Hebei Province, China, suffering from chronic diseases, underscoring the necessity for enhanced attention to chronic disease prevention and management in this group and emphasising the requirement for focused interventions aimed at improving health outcomes.Keywords: civil servants, health status, ultrasound, real-world study, Hebei Province, China